Not only "nurture", but also "nature", influence the outcome of zygoma repair. Issue 6 (December 2013) - Nagasao, Tomohisa; Itamiya, Tomoki; Sakamoto, Yoshiaki; Shimizu, Yusuke; Ogata, Hisao; Jiang, Hua; Kishi, Kazuo; Kaneko, Tsuyoshi
Abstract: The present study aims to elucidate the relationship between preoperative deviation patterns of fractured zygomas and treatment outcomes. Forty-five randomly selected patients with tri-pod type zygoma fractures were classified into a medial rotation group and a lateral rotation group, depending on preoperative deviation patterns. A minimum of 6 months after the operation, symmetry of the cheek was evaluated by three plastic surgeons using a VAS system. The evaluated scores were compared between the two groups. Furthermore, simulation of postoperative secondary deformity was performed by applying hypothetically defined relapse forces on CAD models produced by referring to the CT data of 20 patients. The deviation values obtained by the simulation were compared between the two groups. The results demonstrate that VAS scores were higher for the lateral rotation group than for the medial rotation group and that the deviation values were higher for the medial rotation group than for the lateral rotation group. It is concluded that treatment outcomes of zygoma fractures are affected by preoperative deviation patterns. Cases with medial rotation are likely to present poorer outcomes than those with lateral rotation.